Temporal cuing modulates alpha oscillations during auditory attentional blink. (9th June 2016) - Shen, Dawei; Ross, Bernhard; Alain, Claude
Abstract: Attentional blink (AB) refers to the phenomenon whereby the correct identification of a visual or auditory target impairs processing of a subsequent probe. Although it has been shown that knowing in advance, when the probe would be presented, reduces the attentional blink and increases the amplitude of event‐related potential (ERP) elicited by the probe, the neural mechanism by which attention mitigates the AB remains unclear. Here, we used time‐frequency analysis to further explore the mechanism of the auditory attentional blink. Participants were presented a series of rapid auditory stimuli and asked to indicate whether a target and a probe were present in the sequence. In half of the trials, participants were cued to the probe position relative to the target ('Early' or 'Late'). Probe detection and ERP amplitude elicited by the probe decreased when the probe was presented shortly after the target compared to when it was presented later after the target. Importantly, the behavioral and ERP correlates of probe discrimination significantly improved when the 'Early' cue was presented. The improvement in processing the probe in the cued condition was accompanied by the decrease in alpha activity (8–13 Hz) after the time when the probe was expected; suggesting that successfully directing attention to time window where the probe would likely occur reduces the processing resources needed to suppress distractors. This in turn freed up available processing resources for the target and probe at the short‐term consolidation stage, which ultimately reduced the auditory attentional blink. Abstract : The time‐frequency analysis was used to explore the mechanism of the auditory attentional blink (AB). The reduced AB in the cued condition was accompanied by suppression of alpha activity after the probe presence, suggesting that successfully directing attention to where the probe would likely occur reduces the processing resources needed to suppress distractors. This in turn freed up available processing resources at the short‐term consolidation stage, which ultimately reduced the auditory AB.